Cultivating a Caring Attitude to the Environment and Waste Management in Public Elementary School (SDN) Godog, Garut, Indonesia - Dewi Afrianti (Research Collaboration Community (RCC), 2021)
Environmental problems are often encountered around us, but not everyone feels that these problems must be solved together. The holding of environmental education is expected to make community groups more concerned about cleanliness and health in their surrounding environment. This form of community service at SDN Godog 1 – 2 is carried out due to the fact that the school environment looks unorganized and the lack of waste management around the school. School streets that should look neat and clean are not visible, even around this school road is used as a dumping ground for scattered garbage without any trash cans. The method used in the implementation of this community service is the follow-up study method with a participatory approach. By providing material on the importance of managing waste, proper waste sorting and counseling on the dangers of waste that has polluted the environment. Students are taught directly the practice of managing waste using used bottles as handicrafts, cleaning the school environment and preserving the environment. By carrying out education about caring for the environment, it is hoped that students can play an active role in protecting the school environment by taking part in the practice of cleaning the environment, sorting out used snacks and reducing the use of plastic waste that has been rampant and polluting the surrounding environment. Because with the creation of an attitude of caring for the environment at an early age, it is hoped that environmental problems will reduce this waste and make a generation that loves environmental cleanliness.